Ultra‐small CuO nanoparticles with tailored energy‐band diagram synthesized by a hybrid plasma‐liquid process. Issue 7 (9th March 2017) - Velusamy, Tamilselvan; Liguori, Anna; Macias‐Montero, Manuel; Padmanaban, Dilli Babu; Carolan, Darragh; Gherardi, Matteo; Colombo, Vittorio; Maguire, Paul; Svrcek, Vladimir; Mariotti, Davide
Abstract : CuO is a versatile p‐type material for energy applications capable of imparting diverse functionalities by manipulating its band‐energy diagram. We present ultra‐small quantum confined cupric oxide nanoparticles (CuO NPs) synthesized via a simple one‐step environmentally friendly atmospheric pressure microplasma synthesis process. The proposed method, based on the use of a hybrid plasma‐liquid cell, enables the synthesis of CuO NPs directly from solid metal copper in ethanol with neither surfactants nor reducing agents. CuO NPs films are then used for the first time in all‐inorganic third generation solar cell devices demonstrating highly effective functionalities as blocking layer. Abstract : We report a one‐step green, microplasma‐based synthesis of CuO NPs in ethanol . This simple plasma liquid interaction produces device grade and well dispersed NPs within a few minutes. Furthermore, NPs are characterized without any post‐synthesis treatments and determined their energy band diagram for exploring their functionality in third generation solar cells.